Modeling and simulation of a zero emission urban bus with battery and fuel cell energy systems under real conditions. Issue 2 (12th September 2017) - Alfonsin, Victor; Suarez, Andres; Maceiras, Rocio; Sanchez, Angel
Abstract : This article presents a toolbox for the simulation of a zero‐emission urban bus, which combines batteries and fuel cells. This kind of vehicle performs predefined routes with a certain frequency; hence they are an ideal option for using electric engines fueled by renewable energy systems instead of the combustion engines powered by fossil fuels. The simulation of these vehicles can be made for different standard driving cycles (ECE‐15, EUDC, NEDC, and SFUDS) or for real routes from GPS device data. This will allow considering the orography of the route; considering the slope that overcomes the vehicle at each time, generally this parameter is not included in other models, and it could become a determining factor for the applicability of these vehicles on certain specified routes. Moreover, this tool lets to study and analyze other not easily quantifiable factors, such as the weather or peak‐hour traffic. Finally, the performance of an urban hybrid bus was investigated to assess its theoretical range and the technical feasibility of zero‐emission vehicles. © 2017 American Institute of Chemical Engineers Environ Prog, 37: 832–838, 2018